Synthesis of novel 3′-azido-3′-deoxy-α-L-ribo configured nucleosides: A comparative study between chemical and chemo-enzymatic methodologies. (3rd April 2018) - Rana, Neha; Kumar, Manish; Singh, Ankita; Maity, Jyotirmoy; Shukla, Poonam; Prasad, Ashok K.
GRAPHICAL ABSTRACT: ABSTRACT: Syntheses of novel 3′-azido-3′-deoxy-2′- O, 4′- C -methylene- α- L- ribo furanosyl nucleosides have been carried out from 3′-azido-3′-deoxy-4′- C -hydroxymethyl-β-D- xylo furanosyl nucleosides following both chemical and chemo-enzymatic methodologies. The precursor nucleoside in turn was synthesized from a common glycosyl donor 4- C -acetoxymethyl-1, 2, 5-tri- O -acetyl-3-azido-3-deoxy- α, β -D- xylo furanose, which was obtained by the acetolysis of 4- C -acetoxymethyl-5- O -acetyl-3-azido-3-deoxy-1, 2- O -isopropylidene-α-D- xylo furanose in 96% yield. It has been observed that a chemo-enzymatic pathway for the synthesis of targeted nucleosides is much more efficient than a chemical pathway, leading to the improvement in yield for the synthesis of 3′-azido-3′-deoxy- α- L- ribo furanosyl thymine and uracil from 49 to 89% and 55 to 93%, respectively.